The Effect of English Learning on The Understanding of Sharia Economic Concepts: A Symantic Review - Dina Yulita (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
In the era of globalization, mastery of English is an urgent need for students of Islamic economics to access international literature and understand the latest developments in the field of Islamic finance. This article aims to systematically evaluate the influence of English learning on the understanding of sharia economic concepts. The method used is Systematic Literature Review (SLR) by analyzing ten relevant scientific articles from various national and international journals. The results of the study show that English language learning, especially through the English for Specific Purposes (ESP) approach, has a significant influence on improving academic literacy and students' understanding of the core terms and concepts of sharia economics, such as mudarabah, sukuk, and profit-loss sharing. Reading comprehension and speaking skills have emerged as the most needed skills, in line with the demands of the world of work in the global Islamic finance sector. In addition, the use of interactive learning technologies such as Interactive Flat Panel Displays (IFPD) and digital media has been shown to increase interest in learning and the effectiveness of English teaching in the context of Islamic economics. The findings also reveal that there is a gap between students' linguistic needs and the available syllabus, so a contextual and collaborative redesign of the ESP curriculum is needed. In conclusion, English learning that is designed thematically, contextually, and based on the content of sharia economics plays a crucial role in supporting students' academic and professional readiness at the national and international levels.